2014
DOI: 10.1021/nl502536u
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Single-Particle Tracking of GM1 in Model Membranes Reveals Anomalous Diffusion due to Interleaflet Coupling and Molecular Pinning

Abstract: The biological functions of the cell membrane are influenced by the mobility of its constituents, which are thought to be strongly affected by nanoscale structure and organization. Interactions with the actin cytoskeleton have been proposed as a potential mechanism with the control of mobility imparted through transmembrane “pickets” or GPI-anchored lipid nanodomains. This hypothesis is based on observations of molecular mobility using various methods, although many of these lack the spatiotemporal resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(148 citation statements)
references
References 41 publications
10
131
1
Order By: Relevance
“…A link between GM1, pinning and interdigitation has recently been found in both simulations and model membrane studies (Spillane et al, 2014; Sun et al, 2015). It seems likely that the lo-domain formation observed in the plasma membrane after cross-linking outer leaflet components, described above, causes the pinned molecules to stretch and hence make contact with the inner leaflet lipids, both nucleating and stabilizing the domains.…”
Section: Pinningmentioning
confidence: 68%
“…A link between GM1, pinning and interdigitation has recently been found in both simulations and model membrane studies (Spillane et al, 2014; Sun et al, 2015). It seems likely that the lo-domain formation observed in the plasma membrane after cross-linking outer leaflet components, described above, causes the pinned molecules to stretch and hence make contact with the inner leaflet lipids, both nucleating and stabilizing the domains.…”
Section: Pinningmentioning
confidence: 68%
“…Moreover, a recent study of the SPM dynamic in the cellular PM revealed that instead of clearly partitioning into nanodomains, SPM was mainly transiently trapped51. In the case of the ganglioside GM1, another lipid described as partitioning into L o phases, its transient trapping was shown to depend on molecular pinning and interleaflet coupling between lipid tail domains52. This suggest that Gag could not only generates his own lipid nano-domains at the inner leaflet of the cellular PM but also induce the formation of domains in the outer leaflet of the cellular PM by transiently trapping SPM or other components.…”
Section: Discussionmentioning
confidence: 98%
“…Diffusion of single nanoparticles on supported bilayer membranes has been studied by high-speed iSCAT microscopy before2223. In the previous work, anomalous diffusion, multimobility and also nano-confinements of the particles were observed due to the multiple lipid binding sites on the particle, clustering of the lipids, and the substrate effects, which complicate the investigation of single-molecule dynamics in the membrane.…”
Section: Discussionmentioning
confidence: 99%